Algorithm of the diagnosis and treatment of enteral insufficiency syndrome in peritonitis - E. A. Korymasov; S. A. Ivanov; M. V. Kenarskaya (Вестник хирургии имени И.И. Грекова)
RELEVANCE. The early diagnosis and correction of enteral insufficiency syndrome influence the treatment outcomes in patients with abdominal sepsis and multiple organ failure.The OBJECTIVES was to improve the effectiveness of diagnosis and correction of enteral insufficiency syndrome in patients with generalized peritonitis using the express assessment scale of the severity of enteral insufficiency and the treatment algorithm based on this.MATERIALS AND METHODS. The express assessment scale of the severity of enteral insufficiency syndrome was developed along with the treatment algorithm depending on the detected degree for systematic approach to the management of patients with generalized peritonitis. The study included 39 patients with generalized peritonitis (GP) who had received treatment in the Surgery Department of Samara Regional Clinical Hospital named after V. D. Seredavin in the period of 2019–2020. A computational program was created for quick severity evaluation of enteral insufficiency syndrome and choosing the best treatment strategy.RESULTS. When comparing the severity of enteral insufficiency in patients immediately after the first operation and in 96 hours, a positive dynamics was registered: the number of patients with III degree of severity of enteral insufficiency syndrome decreased from 19 to 4 people, and the number of patients with I degree of severity of enteral insufficiency syndrome changed from 3 to 29 people, this indicated the stabilization of the condition of patients with GP (p<0.05). The statistically significant reduction in the number of points in the limits of each severity was evaluated as the proof of clinical efficacy of the algorithm applied for the enteral insufficiency syndrome correction (p<0.05).CONCLUSION. Due to the correct choice of the treatment algorithm according to the identified severity of enteral insufficiency syndrome, the regression of clinical signs of generalized peritonitis was registered in all patients on the 5th postoperative day (96 hours after surgery).